An Analysis Of Fourth Grade English Textbooks In Elementary School - Dea Khoerunnisa Amelia Deya Amelia (Journal of English Education, Literature and Linguistics, 2023)
Abstract The study is titled "fourth-grade English textbook material analysis ". Titled "my next words grade 4 - student's book for elementary school ". The purpose of the study is to decide whether the content in an English textbook entitled "my next words grade 4 - student's book for elementary school" has the criteria for a good English textbook recommendation from some experts. This textbook analyzes the use of standards based entirely on dictation. Is made up of 4 standards; Materials, language, material presentations and image retrieval of the text book. Qualitative descriptive USES asa study technique to answer the problem of the study. Regarding the statistics collected, the writer concluded that the English textbook "my next words grade 4-student's book for elementary school" has met the remarkable English textbook that is based entirely on what some scholars mean. This suggests that the target of learning has met the criteria of this English textbook. In the book's criteria, there may be one element that does not meet his criteria. And in the practice unit, there are several chapters that don't fit the criteria of a good English textbook. But at maximum they had met the standards of an excellent English textbook. Keywords: Textbook analysis; English textbook